Structural basis for chemokine recognition and receptor activation of chemokine receptor CCR5 - Hui Zhang (Nature Portfolio, 2021)
The chemokine receptor CCR5 plays multiple roles in the immune system. Here, structures of Gi1 protein-coupled CCR5 with or without a chemokine bound and of the CCR5- chemokine MIP-1 α complex offer insight into the distinct binding modes of the ligands and into the mechanism of CCR5 activation.